Low case notification rates of childhood tuberculosis in southern Ethiopia - Dangisso, Mesay Hailu (BMC Pediatr, 2015)
BACKGROUND: Childhood tuberculosis (TB) is a public health concern causing considerable mortality. However, control of childhood TB receives little attention. The control efforts could be inadequate because of challenges associated with difficulties in diagnosing the disease in children. Understanding the burden of the disease among children is important to assess the ongoing transmission of the disease in a community and improving TB control efforts. This study was carried out to assess TB case notification rates (CNRs) and treatment outcomes in children aged less than 15 years over a ten-year period. METHODS: Data were collected from unit TB registers from all health facilities providing TB treatment in the Sidama Zone in Ethiopia. We analysed the CNRs and treatment outcomes by age category, gender, and place of residence. We used logistic regression analysis to identify factors associated with treatment outcomes and to control for confounding. RESULTS: A total of 4,656 cases of children less than 15 years of age were notified as diagnosed and treated for TB, constituting 13 % of all notified TB cases in the study area. The mean CNRs per 100,000 children less than 15 years were 30 for all new cases of TB, 28 for rural cases, 67 for urban cases, 28 in boys, and 32 in girls. The proportions of treatment success were 82 % for new and 77 % for retreatment cases for the entire study period and increased to 93 % for new cases in 2012 (X(2)(trend), P < 0.001). Children less than five years old had a lower treatment success [adjusted odds ratio (AOR) 0.64 (95 % CI, 0.52-0.80)] and higher deaths [AOR 2 (95 % CI, 1.27–3.12)]. The proportion of children who died during treatment among children in the less than 2-year-old age group was three times higher than children in the 2 year and above age groups [AOR 3.34 (95 % CI, 1.92–5.82)]. CONCLUSION: The CNRs of childhood TB were low in Sidama. Children less than 5 years old had a higher proportion of deaths. Efforts need to be made to improve the diagnosis and treatment of TB among children. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12887-015-0461-1) contains supplementary material, which is available to authorized users.